Adsorptive desulfurization of thiophene from the model fuels onto graphite oxide/metal-organic framework composites. (17th January 2018) - Chen, Mingyan; Ding, Yue; Liu, Yucheng; Wang, Na; Yang, Bing; Ma, Lili
ABSTRACT: The composites of a copper-based metal-organic framework (HKUST-1) in the presence of graphite oxide (GO) were synthesized via a solvothermal method to remove thiophene (TP). The prepared GO/HKUST-1 composites were characterization by N2 adsorption-desorption, XRD, SEM. The desulfurization performance of TP from the model fuels by GO/HKUST-1 with different content of GO was investigated. Most importantly, under the optimum adsorptive conditions, the composite material 1.75%GO/HKUST-1 exhibited excellent adsorption capacity of 60.67 mg/g, which was attributed to the highest surface area and porosity.